2014
DOI: 10.1186/s13058-014-0446-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk determination and prevention of breast cancer

Abstract: Breast cancer is an increasing public health problem. Substantial advances have been made in the treatment of breast cancer, but the introduction of methods to predict women at elevated risk and prevent the disease has been less successful. Here, we summarize recent data on newer approaches to risk prediction, available approaches to prevention, how new approaches may be made, and the difficult problem of using what we already know to prevent breast cancer in populations. During 2012, the Breast Cancer Campaig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
244
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(260 citation statements)
references
References 189 publications
(207 reference statements)
3
244
0
3
Order By: Relevance
“…In addition to age, the following are the possible risk factors for breast cancer are: fewer births, later age at first full-term pregnancy, not having breastfed, early age at menarche, irregular menses, late menopause, use of exogenous hormone (e.g. oral contraceptives, combined hormone therapy), obesity, physical inactivity, alcohol consumption, family history of breast cancer are some of the risk factors mentioned above [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to age, the following are the possible risk factors for breast cancer are: fewer births, later age at first full-term pregnancy, not having breastfed, early age at menarche, irregular menses, late menopause, use of exogenous hormone (e.g. oral contraceptives, combined hormone therapy), obesity, physical inactivity, alcohol consumption, family history of breast cancer are some of the risk factors mentioned above [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Millions more people worldwide are probably grossly underestimated because of the poor or inefficient reporting systems and the lack of reliable cancer registries in third-world countries [11] [12]. Substantial advances have been made in the treatment of breast cancer, but the affordance to introduce of these methods to predict cancer at elevated risk level and to prevent this disease is still less successful [13]. Large population-based registry studies have shown that breast cancer prognosis is inherited.…”
Section: Introductionmentioning
confidence: 99%
“…However, other evidence suggest that mTOR may also play a positive role in cancer patients. It has been demonstrated that physical exercise stimulates the mTOR pathway and this is correlated with the prevention of certain type of cancers [34][35][36]. mTOR can also increase tolerability of chemotherapy and can protect against autophagy (frequently associate with cancer resistance to therapy) and improve prognosis [37][38][39].…”
Section: Amino Acids Supplementation As a Cancer Fighting Weaponmentioning
confidence: 99%